Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Bangli - Ni Komang Arini; I Gusti Ayu Intan Saputra Rini; Luh Kade Datrini; I Gusti Agung Prama Yoga (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2023)
The aim of this research is to obtain empirical evidence regarding the factors that influence motor vehicle tax compliance in Bangli Regency. The number of samples used in this research was 100 respondents with the sample determination method using a random sampling method on two-wheeled motor vehicle taxpayers who came from Bangli Regency and were registered to pay motor vehicle tax at the Bangli SAMSAT Office. Data collection was carried out by distributing questionnaires in the form of a Google form. The data analysis technique was carried out using Moderated Regression Analysis. Based on the results of the analysis carried out, it shows that tax knowledge, taxpayer awareness and tax sanctions have a positive effect on motor vehicle taxpayer compliance, and tax socialization is able to strengthen the influence of taxpayer knowledge, taxpayer awareness and tax sanctions on motor vehicle taxpayer compliance at the Office. SAMSAT Bangli Regency.